ANALISIS MANAJEMEN PENANGANAN KELUHAN DI KANTOR PERTANAHAN KOTA SEMARANG - Tatag Puji Wibowo; Ari Subowo; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
The objective of this study is to identify and analyze how the “Kantor Pertanahan Kota Semarang” managing and handling complaints from the public based on the point of view of Management Theory. The method of investigation which is used in this study is descriptive qualitative research method with inductively proceed data analysis.The results of this study indicate that the “Kantor Pertanahan Kota Semarang” complaint management has not implemented properly and correctly. Based on the analysis conducted by the writer, the “Kantor Pertanahan Kota Semarang” is still ignoring some activities in management functions, which ultimately resulted in the lack of maturation and minimum anticipation of planning function. Besides, it also resulted in the overlapping tasks and the functions of the employees as the result of the less maximum of the activity implementation toward the organizing function, as well as weaken the supervision function that resulted in the emergence of the passive working conditions and vulnerably trigger diversion.Based on the results of the study, the suggestions and the solutions that the writer explains in this study, therefore it is expected that those can be used as a suggestion for the “Kantor Pertanahan Kota Semarang” in making policies to improve the quality of the service, especially in the management and handling complaints which furtherly will also be useful for the sake of succeeded implementation of Good Government, i.e. creating a public service which is more professional, effective, efficient, transparent, punctual, adaptive, responsive and accountable to gain the satisfaction and trust from the government public service users.